Accelerated Learning Program Significance, Challenges, and Prospects in Oromia, Ethiopia - Tolera Negassa; Samuel Asnake; Bultosa Hirko (Universal Education Jurnal Teaching and Learning, 2025)
The purpose of this study was to assess the status of the Accelerated Learning Program/ Speed School. The program was designed for children out of school, ages 9 to 14. Respondents were chosen using a purposive sampling technique. Structured interviews were designed to collect data from 105 participants. The findings reveal that parents send their children to the Accelerated Learning Program owing to its contribution. Students are able to complete their literacy skills in a short time and catch up to their age equivalent at grades 4, 3, and 2. Except for some challenges, the program has shown remarkable practices in terms of access, equity, and quality education that can be adopted by formal schools to reach disadvantaged children, children out of school, or dropouts.